2011
DOI: 10.1902/jop.2010.100368
|View full text |Cite
|
Sign up to set email alerts
|

Gingival Overgrowth Among Patients Medicated With Cyclosporin A and Tacrolimus Undergoing Renal Transplantation: A Prospective Study

Abstract: Although there was no statistical difference in the incidences of clinically significant GO after 180 days of immunosuppressive therapy, it was observed that GO occurred later in the Tcr group, and the severity of GO in this group was lower than in patients who used CsA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0
4

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 31 publications
2
20
0
4
Order By: Relevance
“…It is also nephrotoxic, but it results in much less severe hypertension and hypertrichosis. [2432] Various studies have demonstrated less frequent association of gingival overgrowth with the use of tacrolimus than with cyclosporin. [3334] Synergistic effects have been reported when cyclosporin is administered concurrently with calcium channel blockers of dihydropyridine derivatives.…”
Section: Drugs Which Cause Gingival Overgrowthmentioning
confidence: 99%
“…It is also nephrotoxic, but it results in much less severe hypertension and hypertrichosis. [2432] Various studies have demonstrated less frequent association of gingival overgrowth with the use of tacrolimus than with cyclosporin. [3334] Synergistic effects have been reported when cyclosporin is administered concurrently with calcium channel blockers of dihydropyridine derivatives.…”
Section: Drugs Which Cause Gingival Overgrowthmentioning
confidence: 99%
“…DIGO incidence in patients under ciclosporin is more than double than that in patients using tacrolimus or sirolimus. The use of calcium channel blockers has a multiplicative effect in promoting DIGO in patients on ciclosporin (Greenberg et al , 2008; Shiboski et al , 2009b; Cota et al , 2010; Paixão et al , 2011).…”
Section: Drug‐induced Gingival Overgrowthmentioning
confidence: 99%
“…Drug‐induced gingival overgrowth prevalence and severity are assessed through full‐mouth alginate impressions (Seymour et al , 1985). Prevalence in transplant recipients on ciclosporin is high (20–76%) (Greenberg et al , 2008; Shiboski et al , 2009b; Cota et al , 2010; Paixão et al , 2011), markedly lower in the absence of gingivitis (Aimetti et al , 2005, 2008; Kara et al , 2007). Some thus attribute a causative role to dental plaque, and others even consider DIGO a risk factor for dental caries development (Doufexi et al , 2005; Nakib and Ashrafi, 2011), but observational studies fail to support such hypotheses, showing no significant differences between transplant patients with DIGO and controls in parameters such as oral hygiene, gingivitis, and caries (al‐Sarheed et al , 2000; Sheehy et al , 2000; al Nowaiser et al , 2004).…”
Section: Drug‐induced Gingival Overgrowthmentioning
confidence: 99%
“…Thomason et al 15 found a GO prevalence of 47.82% (scores ≥ 30%) when CsA and nifedipine were used in combination, and 37.5% for CsA alone. The results reported by de Oliveira Costa et al 8 and Paixão et al 19 in Brazil revealed significant GO (score ≥ 30%) in 38.1% and 17.4% of CsA-treated patients, respectively. Our study found a lower percentage (8%) of patients using the same GO cut-off; when the cut-off point was lowered to > 10%, the GO prevalence was 17.5%.…”
Section: Discussionmentioning
confidence: 78%